2015
DOI: 10.5709/ce.1897-9254.159
|View full text |Cite
|
Sign up to set email alerts
|

Corruption, Political Instability and Economic Development in the Economic Community of West African States (ECOWAS): Is There a Causal Relationship?

Abstract: Despite the abundant research on economic development, corruption and political instability, little research has attempted to examine whether there is a causal relationship among them. This paper examines the causal relationship among corruption, political instability and economic development in the ECOWAS using the Granger causality test within a multivariate cointegration and error-correction framework for the 1996-2012 period. The findings indicate that political instability Granger-causes economic developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 77 publications
0
27
0
4
Order By: Relevance
“…Researchers have confirmed that corruption increases with political instability (Lederman et al, 2005;Leite and Weidmann, 1999;Park, 2003). Abu et al (2015) examines the causal relationship among corruption, political instability, and economic development in ECOWAS countries within a multivariate cointegration and errorcorrection framework. They find that many years of political instability have contributed to the high rate of corruption and underdevelopment in ECOWAS countries.…”
Section: Robustnessmentioning
confidence: 97%
“…Researchers have confirmed that corruption increases with political instability (Lederman et al, 2005;Leite and Weidmann, 1999;Park, 2003). Abu et al (2015) examines the causal relationship among corruption, political instability, and economic development in ECOWAS countries within a multivariate cointegration and errorcorrection framework. They find that many years of political instability have contributed to the high rate of corruption and underdevelopment in ECOWAS countries.…”
Section: Robustnessmentioning
confidence: 97%
“…H2: Political instability has negative effect on enterprises' innovativeness Rising corruption and political instability contribute to underdevelopment through adversely affecting government revenue, production, savings, investment, growth, and income distribution in West Africa (Abu et al, 2015). Alonso and GarcimartĂ­n (2013) identified that corruption reduces enterprises' innovativeness through increasing distrust and uncertainty in governmental institutions and the entire business environment.…”
Section: H1: Corruption Has Positive Effect On Political Instabilitymentioning
confidence: 99%
“…Corruption has perilous implications for the economies but in developing economies it particularly has detrimental impacts on socioeconomic indicators. In various forms it retards economic growth (Tanzi & Daveoodi, 1998;Mo, 2001;Meon & Sekkat, 2005;Venard, 2013), destabilize governments (Mbaku & Paul, 1989;Abu, Karim & Aziz, 2015), harms foreign direct investment (Habib & Zurawicki, 2002), decreases public and private sector investment (Alesina & Perotti, 1996;Meon & Sekkat, 2005;Mo, 2001), reduces human capital (Mo, 2001), increases poverty (Gupta, Davoodi & Alonso-Terme, 2002) and adversely affects sustainable development (Dietz, Neumayer & De Soysa, 2007;Aidt, 2010;Venard, 2013). However, the corruption may promote economic growth, the idea stems from Leff (1964) and Huntington (1968).…”
Section: Introductionmentioning
confidence: 99%
“…Political instability creates political and bureaucratic corruption. Politically weak governments bribe their rivals and bureaucrats to sustain their governments which penetrate to the gross root level (Abu, Karim & Aziz, 2015). The magnitude of political instability directly and proportionally affects the degree of corruption in the economies (Park, 2003).…”
Section: Introductionmentioning
confidence: 99%